Digital models: How can dental arch form be verified chairside? - Alana Tavares; Emanuel Braga; Telma Martins de Araújo
ABSTRACT Introduction: Plaster dental casts are routinely used during clinical practice to access maxillary dental arch form and assist on fabrication of individualized orthodontic archwires. Recently introduced, digital model technology may offer a limitation for the obtainment of a dental physical record. In this context, a tool for dental arch form assessment for chairside use is necessary when employing digital models. In this regard, paper print of the dental arch seems thus to be useful. Methods: In the present study, 37 lower arch models were used. Intercanine and intermolar widths and dental arch length measurements were performed and compared using plaster dental casts, digital models and paper print image of the models. Ortho Insight 3D scanner was employed for model digitalization. Results: No statistically significant differences were noted regarding the measurements performed on the plaster or digital models (p> 0.05). Paper print images, however, showed subestimated values for intercanine and intermolar widths and overestimated values for dental arch length. Despite being statistically significant (p< 0.001), the differences were considered clinically negligible. Conclusion: The present study suggests that paper print images obtained from digital models are clinically accurate and can be used as a tool for dental arch form assessment for fabrication of individualized orthodontic archwires.